(1502) The use general equilibrium models in medium term planning-Theoretical background-Theoretical background استخدام نماذج التوازن العام في التخطيط متوسط ​​الأجل - الخلفية النظرية - الخلفية النظرية - Zaghloul, Fathia; Nakhla, Afaf (The Institute of National Planning, 2018)

(untitled)
Currently developed countries required a century to industrialize. This transformation involves large and systematic shifts in the structure of production, demand, employment, investement, and trade. Developing countries aim at achieving a similar transformation in a shorter period in an adverse world cirumstances. .